LEGAL CONSEQUENCES OF DEPOSITED FUNDS TO PUBLIC NOTARY BEFORE PREPARATION OF SALES AND PURCHASE AGREEMENT: A Case Study of Supreme Court Decision Number 508 K/PID/2017 - Jayanti, Ni Nyoman Tri; Wesna, Dr. Putu Ayu Sriasih; Puspadma, Dr. I Nyoman Alit (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2024)
Depositing funds to the notary before the preparation of the Sales and Purchase Agreement (PPJB) is a common property transaction in Indonesia. It ensures the safety of the funds prior to the final agreement between the buyer and seller. However, there are legal risks associated with the management and use of these funds, especially if there is a dispute or a violation of the agreement. This research analyzes the legal consequences of entrusting funds to a notary by examining the case of Supreme Court Decision Number 508 K/PID/2017. This decision provides important insights into the responsibilities and obligations of notaries in the context of fund entrustment and its legal implications for the parties involved. This research aims to analyze the legal consequences of deposited money to public notary before making a land sale and purchase agreement. This research uses a normative method through legal approach and legal concept analysis. Data was obtained from relevant regulations and legal literature. The results indicated that if a notary receives money before the agreement is made, he/she acts outside his/her authority as a notary and only as a trustee. If there is any misuse of the money, the notary can be charged with embezzlement under Article 372 of the Criminal Code. This dispute can be resolved through legal channels (litigation) or negotiation and mediation (non-litigation). Depositing funds with a notary before the sale and purchase agreement can have serious legal consequences if it does not fulfill the correct procedure, as shown in Supreme Court Decision Number 508 K/PID/2017.